Policy Analysis of Juvenile Criminal Law: Between Protection and Enforcement - Yanti, Vira (PT. Hafasy Dwi Nawasena, 2024)
This research aims to analyze juvenile criminal law policy in Indonesia, focusing on the challenges and opportunities in its implementation, as well as the contribution of restorative justice principles in handling cases of juvenile offenders. The method used is Systematic Literature Review (SLR), which collects and analyzes literature related to juvenile law policy, in order to understand the gap between existing regulations and practices in the field. The results show that although Indonesia has a strong legal foundation, such as Law No. 11/2012 on the Juvenile Criminal Justice System (SPPA), the implementation of this policy is often not in line with expectations. Many children involved in legal offenses still do not receive adequate protection, both in terms of legal assistance and approaches that prioritize rehabilitation. Law enforcers often lack an understanding of children's rights, while coordination between agencies involved in handling children's cases is not optimal. These findings indicate the need to increase understanding of restorative justice and the protection of children's rights, as well as the need to strengthen cooperation between relevant institutions. With a more comprehensive approach, it is hoped that this policy can be more effective in providing protection and opportunities for children to reintegrate. This research also proposes that Indonesian juvenile criminal law policy should consider stronger educational aspects as a preventive measure, as well as integrating restorative justice principles to improve social relations between children, victims and the community.